THE INFLUENCE OF INDEPENDENCE, PROFESSIONALISM AND GOOD GOVERNANCE ON INTERNAL AUDIT QUALITY: Studies at the Inspectorate of West Bandung Regency - Patria, Gilang; Arismutia, Salza Adzri (Universitas Indonesia Membangun, 2022)
The purpose of this study was to determine the effect of independence, professionalism and good governance of internal auditors on internal audit quality. Data collection was carried out through field research and library research and distributing questionnaires to 52 respondents. Sampling using Non-probability Sampling with Saturated Sampling. To measure the effect of the sample used classical assumption test analysis, multiple linear regression analysis and the coefficient of determination as well as hypothesis testing. Data processing uses the Statistical Product and Service Solution application version 25.The results showed that testing the hypothesis (t test) obtained the following results: (1) Auditor independence has no effect on internal audit quality where count (-0.857) is smaller than table 2.010 with a significance level (-0.857) > 0.05 (2 ) Auditor professionalism has a positive effect on internal audit quality where count is 10.981 greater than table 2.010 and a significance value of 0.000 <0.05 (3) Good Governance has an effect on internal audit quality where count is 9.715 less than table 2.010 and a significance level of 0.000< 0.05. The results of hypothesis testing (f test) independence, internal auditor professionalism and good governance have a positive effect on internal audit quality where the count is 413.551 greater than the table 2.802 with a significance level of 0.000 <0.05.